(untitled) (International Journal of Information Technology and Computer Engineering, 2015)
The possibility for shrinkage-related fault simulation in form castings to aid in the enhancement of cast product quality has prompted much research into the topic. It is currently challenging to measure the magnitude of macroshrinkage, even if its position may be calculated quite readily using contemporary solidification models. There have been many attempts and assertions of accomplishment, but microporosity prediction remains an unsolved mystery. Following a brief introduction to the underlying physics, this paper goes on to discuss the different methods used to model the evolution of macro- and micro-porosity. These methods range from basic thermal models and criterion functions to more advanced models based on oxide entrapment, channel and porous medium, and hydrogen diffusion, respectively